POST-CURE'S EFFECT ON THE DEPTH OF CURE OF A SHORT FIBER-REINFORCED RESIN COMPOSITE - Herda, Ellyza; Ninda, Nadia Safira; Damiyanti, Mia (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to identify post-cure's effect on the depth of cure (DOC) of a short fiber-reinforced resin composite (SFRC). Methods: Six EverX PosteriorTM shade A3 specimens were cured with a light-emitting diode light curing unit with 800 mW/cm2 of light irradiation for 20 s. The specimens were divided into two groups. The first was measured immediately post-cure and the second was measured 24-h post-cure. They were measured with a Vickers microhardness profile test. An independent t-test was used to analyze the significance of the differences between the DOC value and different variables. Results: The DOC of the specimens measured immediately post-cure was 3.02±0.02 mm. The DOC of the specimens measured 24-h post-cure was 3.93±0.03 mm. Conclusion: The DOC of the specimens measured 24-h post-cure was significantly higher than the DOC of the specimens measured immediately post-cure. Post-cure polymerization (24-h post-cure) can increase the DOC values of an SFRC.